The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/eth.13321
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐night territorial behavior, chorus attendance, and mating success in red‐eyed treefrogs

Abstract: For many frog species that aggregate around ponds or streams, chorus attendance, the percentage of time or nights a given male is present and actively calling at an aggregation, is the strongest documented predictor of inter‐male variation in reproductive success in the wild. Males are, thus, thought to compete via endurance rivalry, where available energetic reserves and individual physiology interact to determine chorus tenure. Frogs often exhibit territorial behavior within these aggregations, and territori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Male mate choice has never been studied for red‐eyed treefrogs, to our knowledge; however, a study of male reproductive success in a Panamanian population of red‐eyed treefrogs showed that territoriality and site‐fidelity were strong predictors of male reproductive success (Dougherty et al, 2022). Male–male competition in A. callidryas includes shaking tree limbs to displace other males and to establish territories, wrestling (Caldwell et al, 2010), and amplectant males being pushed off the backs of females by other males (D'Orgeix & Turner, 1995, personal observation).…”
Section: Discussionmentioning
confidence: 99%
“…Male mate choice has never been studied for red‐eyed treefrogs, to our knowledge; however, a study of male reproductive success in a Panamanian population of red‐eyed treefrogs showed that territoriality and site‐fidelity were strong predictors of male reproductive success (Dougherty et al, 2022). Male–male competition in A. callidryas includes shaking tree limbs to displace other males and to establish territories, wrestling (Caldwell et al, 2010), and amplectant males being pushed off the backs of females by other males (D'Orgeix & Turner, 1995, personal observation).…”
Section: Discussionmentioning
confidence: 99%